L’apport des copies de Gaignières à la connaissance des archives de l’abbaye de Longpont - Benoît-Michel Tock (Les Cahiers de l'École du Louvre)
The publication of the charters of the Abbaye de Longpont in the twelfth century is important, since we know of around 200 acts received by this great monastery. But it is a complex task, given the almost total absence of originals, and the fact that only very partial cartularies exist. Fortunately, we have the copying and analysis work carried out by Gaignières: around a quarter of the acts are known to us only through him, which shows just how valuable his contribution is. However, rather than making full (and reliable!) copies, Gaignières favoured partial copies or analyses, depending on what interested him most: the names of families as well as the seals.